Item Selection for a New Health-Related Quality of Life Measure for Parkinson’s Disease: The Preference-Based Parkinson’s Disease Index (PB-PDI) - Selina Malouka; Lizabeth Teshler; Nancy Mayo; Marla Beauchamp; Julie Richardson; Ayse Kuspinar (Neurology Research International)
Background. Parkinson’s disease (PD) is a neurodegenerative condition, predominantly affecting older adults. Preference-based measures (PBMs) can be used to make decisions about the cost-utility of different treatments. There are currently no PBMs for health-related quality of life (HRQoL) for PD. A previous study identified important health domains for individuals with PD and developed an item pool from existing measures per domain. The current study aims to contribute to the development of a new disease-specific PBM of HRQoL for PD by reducing the current pool of items according to the preferences of individuals with PD. Methods. Fifty-three participants completed a visual analogue scale (VAS) of self-perceived health, the prototype PBM measure, and an item importance rating. To reduce the item pool, the following were calculated: (1) inter-item correlations; (2) impact of each item based on item performance and importance rating; (3) directionality of response options by comparing the VAS scores against each item. Results. Participants (male = 54.7%, age = 60.0 ± 10.2) had a median Hoehn and Yahr score of 2.5 (interquartile range = 1). Items supported for inclusion by this analysis were sleep, fatigue, tremor, mood, walking, memory, and dexterity. Items demonstrating a logical decrease in VAS score with each increasing severity level were sleep, memory, tremor, fatigue, and mood. Conclusion. This PBM will be critical for informing decisions about the cost-utility of PD treatments, guiding the resource allocation within our healthcare system. Future research will include cognitive debriefing with individuals with PD to refine item response options.